How Updates in Chicago Classification Impact Clinical Practice. Issue 3 (September 2021) - Yadlapati, Rena; Kahrilas, Peter J.
Chicago Classification version 4.0 (CC v4.0), published in 2021, presents several modifications largely aimed at minimizing over-diagnosis of inconclusive patterns on high-resolution manometry (HRM). These include: (1) introduction of a standardized HRM protocol for consistency among centers, (2) emphasis on the need for supportive data in instances of inconclusive manometric patterns, (3) required presence of relevant symptoms in certain instances to reduce over-diagnosis and inappropriate interventions, and (4) classification as disorders of EGJ outflow or disorders of peristalsis. These updates aim to improve the clinical application of HRM and patient outcomes.